2017
DOI: 10.1111/cyt.12491
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid FNA cytology in Asian practice—Active surveillance for indeterminate thyroid nodules reduces overtreatment of thyroid carcinomas

Abstract: Although Asian thyroid practices have implemented the American Thyroid Association guidelines, significant deviations in actual risk of malignancy (ROM) have been reported. With review of the literature from Asia, the authors examine the underlining reasons for actual ROMs reported in Asia being so different from western practice based on the author's perspective. Although the most popular diagnostic system for thyroid cytology used in Asian countries is the Bethesda system, the Japan Thyroid Association publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 72 publications
2
96
1
Order By: Relevance
“…This web-based scoring system could be used in daily practice to calculate and estimate the risk of malignancy of thyroid nodules on the basis of ultrasound findings and biopsy results. 34 Hong et al 35 suggested repeat biopsy or surgery for AUS/FLUS nodules with intermediate or high suspicion on ultrasound patterns (Korean TIRADS 4 or 5) and a malignant risk ranging from 30%-90%. The areas under the receiver operating characteristic (ROC) curves were 0.837 and 0.773 for the new and old prediction models, respectively nodules according to ultrasound findings, as well as several TIRADS and risk-stratification systems, were all developed for use in thyroid nodule risk stratification using various ultrasound features.…”
Section: Discussionmentioning
confidence: 99%
“…This web-based scoring system could be used in daily practice to calculate and estimate the risk of malignancy of thyroid nodules on the basis of ultrasound findings and biopsy results. 34 Hong et al 35 suggested repeat biopsy or surgery for AUS/FLUS nodules with intermediate or high suspicion on ultrasound patterns (Korean TIRADS 4 or 5) and a malignant risk ranging from 30%-90%. The areas under the receiver operating characteristic (ROC) curves were 0.837 and 0.773 for the new and old prediction models, respectively nodules according to ultrasound findings, as well as several TIRADS and risk-stratification systems, were all developed for use in thyroid nodule risk stratification using various ultrasound features.…”
Section: Discussionmentioning
confidence: 99%
“…This is because there are significant and irreconcilable differences between Asian and Western practices for management of thyroid nodules and thyroid cancer. These differences include the following: (i) Asian patient populations live in mostly iodine sufficient countries and the histological type of the majority of thyroid carcinoma is papillary thyroid carcinoma (PTC); (ii) the prevalence of the BRAF V600E point mutation in Asian PTC cohorts is higher than that reported from Western countries; (iii) it is well‐known that significant numbers of patients with low‐risk papillary microcarcinoma (PMC) are treated conservatively (active surveillance) in Asia instead of by immediate surgery; (iv) resection of indeterminate thyroid nodules is quickly selected in Western practice and diagnostic surgery is more common to prevent missing malignancy due to medicolegal reasons in Western practice; and (v) approaches for low‐risk thyroid carcinoma (lobectomy instead of total thyroidectomy) are more conservative in Asia . Therefore, many important publications from Asia were not well acknowledged in the WHO classification or in most Western clinical guidelines, as those data obtained from Asian practice are not reproducible in current Western practice .…”
Section: Major Revisions To Thyroid Follicular Cell Tumors In the Newmentioning
confidence: 99%
“…Even if they are found to be malignant tumors and adverse events develop, they can be managed curatively as long as they are encapsulated and intrathyroidal tumors (ex0, N0 and M0). In our Asian and Australasian experience, the vast majority of borderline tumors are diagnosed in the benign category (FA), and clinically significant cancers are rarely missed using this conservative approach . However, some intrathyroidal tumors are true malignant tumors and have a non‐negligible risk for structural disease recurrence, such as non‐encapsulated 2‐4 cm PTC (5% of recurrence) and BRAF mutated <4 cm PTC (10% of recurrence), but they can be detected preoperatively by applying a multidisciplinary clinical approach by experienced clinicians and pathologists …”
Section: Follicular Adenoma and Borderline Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This re‐classification provided evidence for limited operation (i.e., lobectomy without lymph node dissection) for NIFTP cases. Furthermore, the Japan Thyroid Association recommended active surveillance without diagnostic surgery for indeterminate thyroid nodules including NIFTP …”
mentioning
confidence: 99%